Transcriptional regulation mechanism of flavonoids biosynthesis gene during fruit development in astragalus membranaceus - Hu, Pengfei; Suriguga,; Zhao, Ming; Chen, Shaoqing; Wu, Xiaohua; Wan, Quan (Frontiers in Genetics, 2022)
Astragalus membranaceus, as an important medicinal plant, are an excellent source of flavonoids. Flavonoid compounds in A. membranaceus has been widely used in medicine and supplement, but known of the molecular mechanism of flavonoid biosynthesis is still very few. Here, we analyzed the association between flavonoid content and gene expression pattern during six different fruit developmental stages. Sixteen gene expression trends were significantly identified, involving 8,218 genes. The gene expression trend in profile 0 was positively correlated with flavonoid content, while the gene expression trend in profile 79 was negatively correlated with flavonoid content at six developmental stages. The expression level of genes involved in general phenylpropane pathway was higher than that of genes involved in flavonoid biosynthesis pathway. A total of 37 genes involved in flavonoid synthesis were identified in A. membranaceus. The expression pattern of flavonoid related genes was highly correlated with flavonoid content. Our study deepened the understanding of flavonoid synthesis mechanism, and provided useful resources for future studies on the high flavonoid molecular breeding of A. membranaceus.